Ablation behavior of tungsten alloys under high-energy electron irradiation - Yiyi Ma; Shangming Chen; Lei Peng; Yongjie Sun; Jingyi Shi; Chengjun Zhu; Zhenyu Wei; Pengfei Zheng; Rui Liu; Wei Jiang; HuiJuan Wang (Nuclear Fusion)
In order to investigate ablation behavior caused by runaway electrons on plasma facing materials (PFMs), the high energy electron irradiation experiment with a pulse duration of 0.6 µ s at room temperature was performed. Specimens of ITER-grade tungsten (W), W-0.5 wt% ZrC alloy (WZC) and potassium-doped tungsten alloy (W–K) were irradiated at different average energy densities. The results indicate that the radial patterns of corrugated and strip-like bulge products on the irradiated specimens’ surfaces are due to the high energy electron pressure. The average void radius, void number density, area and area number density of bulge products on the surface increase with the average energy density in W and W alloys. Second phase particles add more nucleation sites, making void formation and growth easier in W alloys. WZC and W–K have higher average void number density than W. Voids in W alloys, doping of ZrC particles and the fibrous structure of W–K could help enhance heat dissipation and reduce the height of molten layer thickness. Compared to W alloys, W not only has higher area number density and larger area ratio of bulge products on the surface but also exhibits more droplets and larger droplets dimensions. Higher thermal conductivity of W contributes to the higher average molten layer thickness.